Language Style of Delivering Da’wah Messages in the Youtube Channel ZAVILDA TV - Angriani, Rina; Faridah, Faridah (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
The evolution of advanced information technology is relatively fast. Because of this progress, people can now quickly gain knowledge through social media; many people use Youtube media to get information or entertainment. Zavilda TV's YouTube channel features various entertainment options, including experimental social entertainment. This study aims to find out the style of language for conveying da'wah messages in Zavilda TV's YouTube content entitled